The University’s Social Responsibility During the COVID-19 Pandemic: A Case Study - Zrałek , Maria; Kaczmarczyk , Michał (Journal of Public Governance, 2021)
Objectives: The Law on Higher Education and Science as well as the Universities’ Declaration of Social Responsibility promotes the application of the principles of social responsibility in all areas of universities’ activity. These rules are of particular importance during the pandemic, when the crucial fields of universities’ functions are at risk. The article aims at evaluating the actions that the Humanitas University in Sosnowiec has taken during the SARS-CoV-2 pandemic. The adaptation of these activities to the COVID-19 crisis determines the ability to adjust to the challenges of the environment in which the University operates. In the longer term, it also contributes to how the stakeholders assess the extent to which the University implements the idea of social responsibility.Research Design & Methods: This article applies a case-study method. It covers the analysis and synthesis of the activities undertaken by the Humanitas University in Sosnowiec within the researched period. Collecting information employed the analysis of the University’s website, document analysis, survey, in-depth interviews, and participatory observation.Findings: The conducted analyses revealed that the COVID-19 pandemic and the resultant limitations made it possible to develop new forms of crisis management at the University. Internal and external stakeholders have adapted to this new organisational situation. The inclusion of social responsibility rules into the functioning of the University enabled it to preserve its values in both internal and external relations.Implications / Recommendations: The University has implemented the developed recommendations. This allowedthe University to proceed with teaching and maintain actions directed to its socio-economic environment, all of which happened with the use of the University’s social responsibility principles. Thus, these solutions can serve as a model for other universities facing disruptions deriving from crises such as the COVID-19 pandemic.Contribution / Value Added: Our research outcomes contribute to the development of management-related knowledge on how to deal with a crisis in higher education. We identify a significant source of the added value in the considerations on how the implementation of social responsibility rules might protect a university against the unexpected and sudden distortions in its global environment.